Handbook of research on power and energy system optimization - Kumar, Pawan; Singh, Surjit; Ali, Ikbal; Ustun, Taha Selim (IGI Global, Disseminator of Knowledge, 2018)
"This book explores how several optimization techniques involving extensive search, analytical approach and the computational or artificial intelligence. It also explores computational intelligence based on nature inspired meta-heuristic approaches are finding wider acceptance for optimization of discrete problems particularly for large systems with no fixed solution under different operating conditions"...
Includes bibliographical references
Keywords: Electric power systems -- Management -- Data processing -- Handbooks, manuals, etc; Electric power systems -- Mathematical models -- Handbooks, manuals, etc; Mathematical optimization -- Handbooks, manuals, etc; Elektrizitätsversorgung; Elektrische Energie